Relaciones económicas entre América Latina y Estados Unidos : comentarios al trabajo de Aníbal Pinto - Sunkel, Osvaldo (Estudios Internacionales, 1973)
Aníbal Pinto’s work provides an excellent basis for examining some of the changes that have taken place in economic and political relations between Latin America and the United States in recent years, to try to find an interpretation of them, and to scrutinize in future prospects. This constitutes an obvious reality, as Pinto shows: that the North American approaches to these relationships have been undergoing very significant changes. Although unfortunately the work we are commenting on does not examine the other side of the medal –the attitudes of Latin Americans in relation to their hegemonic power–, it is well known that here too there have been changes of the greatest importance.